The ballistic performance of bone when impacted by fragments - Caister, A. J.; Carr, Debra J.; Campbell, P. D.; Brock, Fiona; Breeze, John (Springer, 2020)
Physical models are required to generate the underlying algorithms that populate computer simulations of the effects of explosive fragmenting devices. These models and simulations are used for understanding weapon performance, designing buildings and optimising personal protective equipment. Previous experimental work has investigated the performance of skin and muscle when subjected to fragmentation threats, but limited evidence exists for the performance of bone when impacted by fragments. In the current work, ballistic testing was conducted using two types of internationally recognised steel fragment simulating projectiles (FSPs): (i) 5.5 mm diameter (0.68 g) ball bearing (BBs) and (ii) 1.10 g chisel nosed (CN). These projectiles were fired at isolated swine ribs at impact velocities between 99 and 1265 m/s. Impact events were recorded using a high-speed camera. Selected specimens were analysed post-impact with plain x-radiographs and micro-CT scanning to determine damage to the bone architecture. Bones were perforated with a kinetic energy density (KED) as low as 0.14 J/mm2. Energy transfer to the bone was greater for the CN FSPs, resulting in increased bone damage and the production of secondary bone fragments. The manner in which the bones failed with faster velocity impacts (> 551 m/s; KED > 6.44 J/mm2) was analogous to the behaviour of a brittle material. Slower velocity impacts (< 323 m/s; KED < 1.49 J/mm2) showed a transition in failure mode with the bone displaying the properties of an elastic, plastic and brittle material at various points during the impact. The study gives critical insight into how bone behaves under these circumstances.
Keywords: swine ribs; armour design; wound ballistics; micro-CT